(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Educational institutions, determining one of the key priorities of their activities to preserve the physical, mental, spiritual and social health of students, lay the foundations for their successful self-realization in the future. In this context, the implementation of military sports games in the educational process of general secondary education institutions (in particular, in physical education classes) and in extracurricular activities (when conducting educational activities, contests, competitions, etc.) has great potential for the formation of health-preserving competence of children and students young people The article substantiates the possibilities of military sports games as an effective tool for the formation of health-saving competence in children and school youth. A number of characteristics of military sports games in the context of health-preserving competence have been determined (the presence of requirements for the physical and moral-willed qualities of the participants; a valuable component; a wide range of forms and methods of work (for the development of the cognitive, physical and moral-willed spheres of the individual); variability of use means and methods in the process of health-saving competence; the applied nature of the tasks, the performance of which is easily integrated into the practical activity; the imitative nature of certain elements of the game, which are close to real situations. Examples of military sports games are given (All-Ukrainian children’s and youth military-patriotic game «Falcon» («Jura»), All-Ukrainian (International) gathering-competition of young rescuers «Safety School», All-Ukrainian physical culture and patriotic festival of schoolchildren of Ukraine «Cossack Gart» National Children’s - youth military sports game «Horting-Patriot»), which have proven their effectiveness and expediency for their implementation in the practice of general secondary education institutions. The effectiveness of military sports games as a tool for the formation of health-saving competence of children and school youth is determined by a number of advantages (physical activity, self-control and stress resistance, planning, tactical and strategic thinking, social interaction, leadership and multifunctionality, adaptability).